2019
DOI: 10.1073/pnas.1911429116
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal dysfunction in autism displayed by altered motility and achalasia in Foxp1 +/− mice

Abstract: Gastrointestinal dysfunctions in individuals with autism spectrum disorder are poorly understood, although they are common among this group of patients. FOXP1 haploinsufficiency is characterized by autistic behavior, language impairment, and intellectual disability, but feeding difficulties and gastrointestinal problems have also been reported. Whether these are primary impairments, the result of altered eating behavior, or side effects of psychotropic medication remains unclear. To address this question, we i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
30
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…For PG + M, two of the significantly associated SNPs, 19:18793695 and rs13097265, have been previously linked to Barrett’s esophagus and esophageal adenocarcinoma 82 (Supplementary Table 4 ). rs13097265 is located ~60 kb from the FOXP1 gene, and recently a mouse study 83 has shown that Foxp1 protein is expressed in all layers of the murine GI tract (including the myenteric plexus, which is part of the enteric nervous system and regulates gut peristalsis and transit). Altered motility and achalasia has been observed in Foxp1 +/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…For PG + M, two of the significantly associated SNPs, 19:18793695 and rs13097265, have been previously linked to Barrett’s esophagus and esophageal adenocarcinoma 82 (Supplementary Table 4 ). rs13097265 is located ~60 kb from the FOXP1 gene, and recently a mouse study 83 has shown that Foxp1 protein is expressed in all layers of the murine GI tract (including the myenteric plexus, which is part of the enteric nervous system and regulates gut peristalsis and transit). Altered motility and achalasia has been observed in Foxp1 +/− mice.…”
Section: Discussionmentioning
confidence: 99%
“…Amongst the results we found enrichment for neuromuscular and cardiac function in STRING analysis (S9-20). Some animal models such as FOXP1 , SHANK3 , NOS1 and CHD8 [ 74 , 92 , 94 , 96 , 97 ] have been developed for functional analysis of ASD candidate genes in the gastrointestinal system, which indicates that ASD genes may play an important role in this organ [ 95 ], and yet most research have been mainly focused on the brain in both human and animal models. A greater utilisation of the animal models to explore other systems such as the cardiac and gastrointestinal systems would be welcome.…”
Section: Discussionmentioning
confidence: 99%
“…Our Scn2a gtKO/gtKO mice had a similar ~15% reduced body weight compared to WT throughout life, but close to 80% of Scn2a gtKO/gtKO mice survive to adulthood. Another mouse model of neurodevelopmental disorder, Foxp1 -/-, also has failure to thrive at weaning unless a soft, highcalorie diet is provided [36] which we similarly provided a gel-based high-calorie food source. The combined phenomenon of failure to thrive in adolescence and overeating in adulthood in humans is also evident in Prader-Willi syndrome [37].…”
Section: Discussionmentioning
confidence: 99%